2022
DOI: 10.3390/ph15080921
|View full text |Cite
|
Sign up to set email alerts
|

Copper (I)-Chloroquine Complexes: Interactions with DNA and Ferriprotoporphyrin, Inhibition of β-Hematin Formation and Relation to Antimalarial Activity

Abstract: A new Cu(I)-chloroquine (CQ) complex [Cu(CQ)(PPh3)2]NO3 (1) was synthesized and characterized, and its mechanism of action studied concomitant with the previously reported complex [Cu(CQ)2]Cl (2). These copper (I) coordination compounds can be considered as potential antimalarial agents because they show better inhibition of the CQ-resistant strain in in vitro studies than CQ alone. In comparison with other metal-CQ complexes, only the gold complex was similar to (1), i.e., more active than CQ against both CQ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Amongst the several reports on the anticancer and antiparasitic potential of copper complexes, only a small number of them include Cu(I) as central ion, mainly due to the difficulty to stabilize copper(I) species. However several examples of Cu(I) complexes involving P‐donor ligands and N,N‐diimine chelates have shown high stability and antineoplastic activity in vitro against several tumor cell lines [32,37–46] . In fact, due to the soft nature of the P‐donor and S‐donor atoms, the use of phosphane and sulfur ligands can be an efficient way to stabilize Cu(I)‐d 10 metal centers [46] …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Amongst the several reports on the anticancer and antiparasitic potential of copper complexes, only a small number of them include Cu(I) as central ion, mainly due to the difficulty to stabilize copper(I) species. However several examples of Cu(I) complexes involving P‐donor ligands and N,N‐diimine chelates have shown high stability and antineoplastic activity in vitro against several tumor cell lines [32,37–46] . In fact, due to the soft nature of the P‐donor and S‐donor atoms, the use of phosphane and sulfur ligands can be an efficient way to stabilize Cu(I)‐d 10 metal centers [46] …”
Section: Introductionmentioning
confidence: 99%
“…Some of us have been focused on the search for new Cu(I)–phosphane compounds with several heteroaromatic ligands as anticancer agents. Several complexes of general formula [Cu(PP)(LL)][BF 4 ] in which PP represents mono/bidentate phosphane ligands and LL represents N,N‐, N,O‐ or N,S‐heteroaromatic bidentate ligands were designed and synthesized [18,44–46] . Most of these compounds present high cytotoxic activities in vitro against several human cancer cell lines (e. g. A2780, MCF7, MDAMB231, HCT116 and HCT116 DOXR), in most cases, showing lower IC 50 values than cisplatin [18,44–46] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cu(I) coordination compounds, despite the oxidative instability of the ions [ 19 ], have been studied as potential antitumor [ 20 ] and antimicrobial agents as well [ 16 , 17 ]. For instance, in 2022, Villarreal et al presented the synthesis, structural, and biological studies of a new Cu(I) complex that was shown to be a potential antimalarial drug [ 21 ].…”
Section: Introductionmentioning
confidence: 99%